"Migratory beekeeping and its influence on the prevalence and dispersal of pathogens to managed and wild bees". (August 2022) - Martínez-López, Vicente; Ruiz, Carlos; De la Rúa, Pilar
Abstract: Demand for food is growing along with the human population, leading to an increase in plant production. Many crops are pollinated by insects, so the global demand for managed pollinators is also increasing. The honey bee has traditionally been considered the main provider of crop pollination services. For providing it beekeepers seasonally transport hives to different locations after the flowering of different crops. These movements could be detrimental to pollinators by: i) stressing honey bees, making them more susceptible to pathogens and parasites; ii) spreading bee parasites and pathogens across locations; iii) increasing the transmission of parasites and pathogens between managed and wild pollinators and vice versa (spillover and spillback, respectively). To understand the impact of migratory beekeeping on bee health, we conducted a systematic review to identify the main trends and provide a complete picture of existing knowledge on the subject. We found 52 studies analysing pathogen-related impacts of migratory beekeeping on honey bees. However, only 16 investigations tested the effect of migratory practices on the prevalence and spread of pathogens and parasites. We found no studies that assessed the impact of migratory beekeeping on the occurrence and spread of pests and diseases in wild bees. In general, migratory beekeeping tends to increase the prevalence of pathogens and parasites in honey bee colonies. However, the results were very heterogeneous, probably due to several uncontrolled underlying factors such as management, biological and geographical factors, and the interactions between them. In conclusion, there is an urgent need for studies to assess the impact of migratory beekeeping on bee health, given the current global bee decline and the expected increase in migratory beekeeping due to climate change and crop pollination demand. Graphical abstract: Image 1 Highlights: Migratory beekeeping may affect the health of both managed and wild bees. Only 16 studies compare the prevalence of pathogens between migratory and stationary hives. Results are heterogeneous due to the complex interaction of the underlying factors. Overall, the prevalence of pathogens and parasites increased in migratory honey bees. The impact of migratory beekeeping on the health of wild bees is unknown.